The Tbx20 homologs midline and H15 specify ventral fate in the Drosophila melanogaster leg. - Svendsen, P.C.; Formaz-Preston, A.; Leal, S.M.; Brook, W.J. (Development, 2009)
Regional fates in the developing limbs of Drosophila melanogaster are controlled by selector gene transcription factors. Ventral fate in the fly leg is specified by the expression of the ligand Wingless. We present evidence that midline and H15, members of the Tbx20 class of T-box transcription factors, are key mediators of the Wingless signal in the formation of the ventral region of the fly leg. midline and H15 are restricted to identical ventral domains of expression through activation by Wingless and repression by the dorsal signal Decapentaplegic. midline and H15 function redundantly and cell autonomously in the formation of ventral-specific structures. Conversely, midline is sufficient to induce ventral fate. Finally, the induction of ectopic ventral fate by mid is compromised when Wingless signaling is attenuated, suggesting that Wingless acts both upstream and in parallel with midline/H15 to specify ventral fate. Based on these results, we propose that midline and H15 may be considered as the selector genes for ventral leg fate.